What Makes a Sustainable City? : Sampling of Global Case Studies Highlighting Innovative Approaches to Sustainability in Urban Areas - Santos, Valerie; Gashi, Drilon; Armendaris, Fernando (World Bank, Washington, DC, 2016)
The majority of the world is now urban. Cities are attracting people because they are centers for economic activity and can offer a higher quality of life: there are more jobs, more services available, transport options to move within the city, trade, knowledge exchange, and connections to other cities and countries. As a result, in 2050, two-thirds of the world population is expected to live in cities. Cities around the world are implementing innovative ideas to efficiently manage urbanization. They are facing challenges head on and placing themselves on a path toward sustainability. Increasingly, city governments are becoming empowered administratively and financially to be able to serve their growing populations, offering good public transport options, access to clean water, effective waste management, and other essential basic services. This booklet of case studies showcases cities in developing countries that are implementing bold ideas with the objective of achieving environmental, economic and social sustainability. In all the stories included, the World Bank Group has been able to work alongside the cities to help them meet their goals by offering a number of services. These case studies show what a wide variety of cities have achieved in this endeavor, with clear and measurable results. Cities have responded to the new challenges and opportunities of rapid urbanization by spurring innovation to improve services, create jobs, and enhance livability for future generations.